1996
DOI: 10.1192/bjp.169.6.747
|View full text |Cite
|
Sign up to set email alerts
|

Early Compliance and Other Factors Predicting Outcome of Exposure for Obsessive–Compulsive Disorder

Abstract: The strongest and most consistent predictor of better outcome to weeks 9 and 32 was compliance with exposure and ritual prevention in the first week of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 20 publications
7
44
0
6
Order By: Relevance
“…We found two RCTs of behavioural therapy (total 96 adults [mean ages 35 and 33 years]; duration 2.5 months and 32 weeks) [33] [34] and two retrospective cohort studies (total 346 adults [mean ages 36 and 34 years]; duration 1 year and 11 weeks), [35] [36] which assessed factors predicting outcome. These found that poorer outcome was predicted by initial severity, depression, longer duration, poorer motivation, and dissatisfaction with the therapeutic relationship.…”
Section: Commentmentioning
confidence: 99%
“…We found two RCTs of behavioural therapy (total 96 adults [mean ages 35 and 33 years]; duration 2.5 months and 32 weeks) [33] [34] and two retrospective cohort studies (total 346 adults [mean ages 36 and 34 years]; duration 1 year and 11 weeks), [35] [36] which assessed factors predicting outcome. These found that poorer outcome was predicted by initial severity, depression, longer duration, poorer motivation, and dissatisfaction with the therapeutic relationship.…”
Section: Commentmentioning
confidence: 99%
“…Por outro lado, Araújo et al 29 , em um ensaio clínico randomizado, não identificaram o gênero como possível preditor de resultado no tratamento de 46 pacientes ambulatoriais com TOC, tratados por 9 semanas com duas formas de terapia de EPR (exposição in vivo ou imaginária + in vivo).…”
Section: Gênerounclassified
“…In short, the theory assumes that OCD is acquired by way of learning and habituation within the patient. From past trauma and/or unwanted experiences, an individual may begin to "learn" or associate relatively harmless stimuli with anxiety (De Araugo et al, 1996). For instance, a person may become anxious about touching cars after being involved in a major car accident.…”
Section: Causes Of the Problemmentioning
confidence: 99%
“…For example, why are so many people "Washers/ Cleaners"? What common traumatic events could have shaped all of these people to be similar in their OCD (De Araugo et al, 1996))?…”
Section: Causes Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation